2014
DOI: 10.1186/1478-7547-12-26
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics model of cervical cancer vaccination and screening interventions in Kenya

Abstract: Objectives: This paper presents a simulation model for evaluating the possible effects of a screening and vaccination campaign against Human Papillomavirus [HPV] in Kenya.Method: A System Dynamics model was developed using the iThink™ computer simulation package. The model was based on data extracted from epidemiological, demographic and published research and where data was not available, expert opinion was sought. The deterministic model stratified the population by vaccination status, screening status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…HPV vaccination commenced in Kenya in 2019 with the initial aim to target 800,000 ten-year-old girls [9]. Kivuti-Bitok et al (2014) assessed the impact of vaccination and screening on cervical cancer rates in Kenya [41]. They found that a secondary vaccination, i.e.…”
Section: Prevention Of Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…HPV vaccination commenced in Kenya in 2019 with the initial aim to target 800,000 ten-year-old girls [9]. Kivuti-Bitok et al (2014) assessed the impact of vaccination and screening on cervical cancer rates in Kenya [41]. They found that a secondary vaccination, i.e.…”
Section: Prevention Of Cervical Cancermentioning
confidence: 99%
“…They found that a secondary vaccination, i.e. targeting women up to 44 years of age who missed the primary vaccination for girls who are not yet sexually active (9-12 years), was the most important intervention, accounting for a more than 50% reduction in incidence rates [41]. This would necessitate education campaigns to make all women aware, a roll-out strategy for those secondary immunisations, and the financial ability to do so.…”
Section: Prevention Of Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the more recent studies have used these models. [40][41][42] However, if the research question involves the assessment of the cost-effectiveness of bivalent HPV vaccination among girls alone (and not including boys), then static progression models that follow the costs and outcomes in a population cohort are considered to yield valid results. 39 The majority of HPV cost-effectiveness analyses for girls that are undertaken globally have used this type of modeling approach and are recommended to answer the policy question.…”
Section: Strengthsmentioning
confidence: 99%
“…Some of the other SD cancer‐screening modeling studies include Kivuti‐Bitok et al . (2014) who developed a model for cervical cancer vaccination and screening interventions in Kenya; Palma et al . (2016) who replicated the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial (PLCO) for serum PSA screening for prostate cancer; and Fett (2001) who replicated the Swedish two‐county trial of mammographic screening for breast cancer, which are all population‐level models.…”
Section: Introductionmentioning
confidence: 99%